The Impact of Non-Tariff Measures to Intra-Association of Southeast Asian Nations Import - CHANTHANASINH, Vadsana; WONGPIT, Piya (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Currently, import tariff reduced globally. NTMs are becoming an increasingly important tool in determining access to markets. Therefore, the objectives of this study are to examine an overview of changes in import competition within the Association of Southeast Asian Nations (ASEAN) member countries, the tuning of the Commodity Frequency Index with NTMs (FI), and the Coverage Ratio (CR) of goods in order to study the effects of non-tariff measures (FI and CR) on the imports among the ASEAN member states. By using Gravity Model with Fixed Effect and Random effect method use Log-Linear Model for analysis with STATA 15. The study showed that ASEAN members’ import in 2019 is 21.5 percent of total ASEAN’s import. Singapore's import is the largest in ASEAN, followed by Malaysia in 2019, hile the imports of Brunei, Lao PDR and Cambodia are among the smallest sizes in the ASEAN member countries. In addition, the most of the list of products that were imported in 2019 were products code HS 27, code HS 85, and code HS 84. Coverages ratio (CR) for imports face higher NTMs incidence rates than the Frequency Index (FI), which affects at least one NTMs and Singapore has the highest frequency index and coverage ratio in the ASEAN member countries from 2014-2019 and followed by Myanmar and Thailand from 2017 on wards. The results suggest a positive impact of the border trade, real GDP of exporter countries, real GDP of importer countries on the export while the negative impact of the distance between trading partners. The Frequency Index that have a positive impact on the import which affects the imports among the ASEAN member states.